Composites materials for food packaging - Cirillo, Giuseppe, 1980-; Kozlowski, Marek A., 1945-; Spizzirri, Umile Gianfranco (Insights into modern food science, 2018)
"The book is intended as an overview on the recent and more relevant developments in the application of composite materials for food packaging applications, emphasizing the scientific outcome arising from the physico-chemical properties of such engineered materials with the needs of food quality and safety. Consumers are increasingly conscious of the strong relationship between food quality and health, and thus the request of packaging materials allowing the quality and safety of foods to be highly preserved. As a result, scientists from both academia and industry work to increase the quality of the food storage, with this book meant as a link between scientific and industrial research, showing how the development in composite materials can impact the field. In the book, the inorganic materials employed for the preparation of composite material is extensively analyzed in terms of physico-chemical properties, environmental and reusability concerns, as well as food interaction features, highlighting the importance and the potential limitations of each approach"--Provided by publisher.